The effect of expansions in maternity leave coverage on children's long-term outcomes - Christian Dustmann; Uta Schönberg (Institute for the Study of Labor (IZA), 2008)
This paper evaluates the impact of three major expansions in leave coverage in Germany on the long-run education and labor market outcomes of children. Evaluation of three policy reforms as opposed to a single reform enables us to analyze whether the impact of paid leave differs from that of unpaid leave, and whether an expansion of a relatively short leave period is more beneficial to child development than an expansion of an already long leave period. Our empirical analysis combines two large administrative data sources on wages, unemployment, and school outcomes. We identify the causal impact of the reforms by comparing outcomes of children born shortly before and shortly after a change in maternity leave legislation, and therefore require substantially weaker assumptions for identification than existing studies. We find little support for the hypothesis that an expansion in maternity leave legislation improves children's outcomes. Given the precision of our estimates, we can statistically rule out the hypothesis that the expansion in paid leave from 2 to 6 (unpaid leave from 18 to 36) months raised wages (attendance at high track schools) by more than 0.3 % (0.1 %).
urn:nbn:de:101:1-20080723162
Keywords: J13; 330; Maternity leave; child development; Mutterschutz; Wirkungsanalyse; Kinder; Bildungsertrag; Deutschland